The Effect of Thai Massage and Sport Massage on Decreasing Low Acids and Blood Glucose - Wulan Fitri Utami, Wulan Fitri; Nurkholis, Nurkholis; Mintarto, Edy (Universitas Negeri Semarang, 2017)
The purpose of this research was to analyze the difference between the effectiveness of Thai and Sports massage against the decrease of lactic acid and blood glucose. The research was experimental laboratoris. The results showed the initial data retrieval on lactic acid level in treatment and control group ranged between between 1.30-3.40 mmol/l of lactate. Then on lactic acid level after activities on Sport massage group was 6.01 mmol/l, whereas the thai massage group was 5.72 mmol/l, and control group was 5.18 mmol/l. whereas in lactic acid levels after 5 minutes of physical activity on a group of sport massage namely 8.36 mmol/l , a group of thai massage 7.26 mmol/l, and the control group 5.83 mmol/l. lactic acid levels and then 10 minutes of physical activity on the group after group of sport massage namely 3.81 mmol/l, a group of thai massage 4.11 mmol/l, and the control group 4.62 mmol/l. While on initial data retrieval on the blood glucose levels between 75 – 91 mg/dL. then in blood glucose levels after activities on a group of sport massage namely 93.50 mg/dL, while the Group of thai massage 96.12 mg/dL, and the control group 88.75 mg/dL. While in blood glucose levels after 5 minutes of physical activity on a group of sport massage i.e. namely 89.75 mg/dL, a group of thai. massage 88.25 mg/dL and a control group of 88 mg/dL. Then blood glucose after 10 minutes of physical activity on the group the Group of sport massage i.e. namely 81.12 mg/dL, a group of thai massage 83.12 mg/dL, and the control group 85.00 mg/dL. Based on the above analysis, it can be concluded that there is a decrease in the levels of blood glucose and lactic acid for each experimental and control groups group after being given the treatment of Thai Massage and Sports Massage.